The Use of Interactive Formative Assessment in an EFL Class Through The Comment Column of Google Classroom - Asifa Dhearul Janah; Desi Wijayanti Ma'rufah; Maulana Mualim (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2022)
Interactive formative assessment was applied in an online teaching-learning. In SMA Annuriyah Bumiayu, an English teacher used Google Classroom in the Comment Column features to apply the online assessment for the EFL students. This study aimed to describe the use, find out the strengths, and discover the weaknesses of interactive formative assessment in the comment column of Google Classroom. This research was descriptive qualitative research. The data were obtained through interviews, observation, and documentation. The data were in the form of interview transcripts, table observation, field notes, and picture documentation. The researcher used data triangulation and method triangulation for the trustworthiness of the data. For analyzing data, the researcher used interactive model analysis, which contained reducing, presenting, and drawing or verification of the data. The results of this research show that the teacher used Google Classroom for presenting interactive assessments. From the description, the finding demonstrates the utilities and the tools of interactive assessment. Furthermore, the finding of the study also exposes the strengths and weaknesses of using Google Classroom. The advantages include Google Classroom is helpful in ELT, assessing students, and managing formative assessment. Also, the disadvantages are students with lack of motivation and low adversity quotient faced on Google Classroom.